2014
DOI: 10.1088/2041-8205/781/2/l30
|View full text |Cite
|
Sign up to set email alerts
|

DISCOVERY OF Hα EMISSION FROM THE CLOSE COMPANION INSIDE THE GAP OF TRANSITIONAL DISK HD 142527

Abstract: We utilized the new high-order 585 actuator Magellan Adaptive Optics system (MagAO) to obtain very high-resolution visible light images of HD142527 with MagAO's VisAO science camera. In the median seeing conditions of the 6.5m Magellan telescope (0.5 − 0.7′′), we find MagAO delivers 24-19% Strehl at Hα (0.656 µm). We detect a faint companion (HD142527B) embedded in this young transitional disk system at just 86.3±1.9 mas (~12 AU) from the star. The companion is detected in both Hα and a continuum filter (∆mag=… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
203
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(221 citation statements)
references
References 38 publications
17
203
1
Order By: Relevance
“…Recently, several discoveries of (candidate) low-mass companions (low-mass stars and protoplanets) embedded in the circumstellar disk of young stars were announced: around LkCa 15 (Kraus & Ireland 2012), HD 142527 (Biller et al 2012), HD 100546 (Quanz et al 2013), and HD 169142 (Reggiani et al 2014;Biller et al 2014). While the exact nature of some of these sources needs to be further investigated, some of these objects are probably indeed observed in the act of formation as indicated by the Hα emission of LkCa 15 b Sallum et al (2015) (see also HD 142527B, Close et al 2014). This warrants an extension of the M − L relation to the formation phase.…”
Section: The Planetary Mass -Luminosity Relationmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, several discoveries of (candidate) low-mass companions (low-mass stars and protoplanets) embedded in the circumstellar disk of young stars were announced: around LkCa 15 (Kraus & Ireland 2012), HD 142527 (Biller et al 2012), HD 100546 (Quanz et al 2013), and HD 169142 (Reggiani et al 2014;Biller et al 2014). While the exact nature of some of these sources needs to be further investigated, some of these objects are probably indeed observed in the act of formation as indicated by the Hα emission of LkCa 15 b Sallum et al (2015) (see also HD 142527B, Close et al 2014). This warrants an extension of the M − L relation to the formation phase.…”
Section: The Planetary Mass -Luminosity Relationmentioning
confidence: 99%
“…If the planetary and stellar accretion rates are of the same order of magnitude as suggested by hydrodynamic simulations (Lubow & D'Angelo 2006), then the independency of R on M for cold accretion can be used to estimate, via L est , the planet's mass pro- vided that L shock can be observationally obtained. This approach (see also Kraus & Ireland 2012;Close et al 2014) then yields a constraint on the planet's mass besides other indicators such as the gap morphology (e.g., Kanagawa et al 2015) or the local disk temperature (Montesinos et al 2015) and scale height (Klahr & Kley 2006). For hot accretion it is more complex to estimate the planet's mass in this way, as the radius becomes then also a function of mass (Fig.…”
Section: The Planetary Mass -Luminosity Relationmentioning
confidence: 99%
See 2 more Smart Citations
“…SDI was first used on the Canada France Hawaii Telescope (CFHT) with the TRIDENT camera (Marois et al 2000(Marois et al , 2003a, with NaCo on the Very Large Telescope (VLT/NaCo; Lenzen et al 2003;Rousset et al 2003) and with the Multiple Mirror Telescope (MMT) A&A 581, A80 (2015) by Close et al (2005) and Biller et al (2007). Recently, Close et al (2014) confirmed a close-in companion around HD 142527 with SDI with MagAO, based on a detection of the Hα emission, not a molecular absorption. However, SDI is limited by differential aberrations between the two channels, which create quasi-static speckles that cannot be removed.…”
Section: Introductionmentioning
confidence: 99%